2018
DOI: 10.1111/wvn.12275
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Pathways to Quality of Life and HbA1c in Patients With Diabetes: A Longitudinal Study That Inform Evidence‐Based Practice

Abstract: Enhancing QoL is important to improve HbA1C levels. Enhancing self-care behaviors is essential to improve subsequent HbA1C control and QoL. Reducing diabetes distress is crucial to improve subsequent QoL. Improving social support is suggested a favorable strategy to reduce diabetes distress and enhance subsequent self-care behaviors in patients with T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
30
2
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 48 publications
8
30
2
2
Order By: Relevance
“…It may also reflect the mental empowerment gained through proactive diabetes education and may reflect physical discomforts of increased regime complexity [33]. Enhancing self-care behaviors is essential to improve HbA1C control and quality of life [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may also reflect the mental empowerment gained through proactive diabetes education and may reflect physical discomforts of increased regime complexity [33]. Enhancing self-care behaviors is essential to improve HbA1C control and quality of life [34].…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the obtained results, it could be concluded that the coronavirus pandemic has a markedly negative impact on the quality of life of diabetics, but the domain of mental quality of life is preserved. Educational plans that improve or include strategies to enhance patient's quality of life may increase compliance, thereby improving these patients' diabetes parameters [48], which is then associated with improved quality of life [32][33][34], and a good educational plan includes all these parameters [40].…”
Section: Discussionmentioning
confidence: 99%
“…The excess in the production of free radicals is among the main indicators of malignant cell development. A number of investigations demonstrated that antioxidants produced by plants can act in scavenging free radicals and regulating the impacts associated with oxidative stress [2]. The effectiveness of different plant-extracted materials toward proliferating cells is well established.…”
Section: Introductionmentioning
confidence: 99%
“…Although A1C levels and QoL are considered physical and psychosocial outcomes of diabetes management respectively (ADA, 2020), the possible causal relationship between A1C and QoL has no consistent determination. A structural equation modeling revealed that D-QoL affected concurrent A1C levels, but A1C levels did not affect concurrent D-QoL in people with type 2 diabetes (Hsu et al, 2018). Therefore, D-QoL might directly associate with concurrent A1C levels and subsequent A1C levels while still requiring a prospective design to analyze and validate.…”
mentioning
confidence: 99%